VD_FINDINFO HC / 2014 / 677 vom 12. Dezember 2014 - VD Tribunal cantonal (2014)
EXPERTISE, FRAIS D'EXPERTISE | 242 CPC, 184 al. 3 CPC (CH), 319 let. b ch. 1 CPC (CH), 320 CPC (CH), 327 CPC (CH), 405 al. 1 CPC (CH)